Rubicon inhibits autophagy and accelerates hepatocyte apoptosis and lipid accumulation in nonalcoholic fatty liver disease in mice. Issue 6 (21st October 2016) - Tanaka, Satoshi; Hikita, Hayato; Tatsumi, Tomohide; Sakamori, Ryotaro; Nozaki, Yasutoshi; Sakane, Sadatsugu; Shiode, Yuto; Nakabori, Tasuku; Saito, Yoshinobu; Hiramatsu, Naoki; Tabata, Keisuke; Kawabata, Tsuyoshi; et al.
Abstract : Nonalcoholic fatty liver disease (NAFLD) is the most prevalent liver disease worldwide. It encompasses a spectrum ranging from simple steatosis to fatty liver with hepatocellular injury, termed nonalcoholic steatohepatitis. Recent studies have demonstrated hepatic autophagy being impaired in NAFLD. In the present study, we investigated the impact of Rubicon, a Beclin1‐interacting negative regulator for autophagosome‐lysosome fusion, in the pathogenesis of NAFLD. In HepG2 cells, BNL‐CL2 cells, and murine primary hepatocytes, Rubicon was posttranscriptionally up‐regulated by supplementation with saturated fatty acid palmitate. Up‐regulation of Rubicon was associated with suppression of the late stage of autophagy, as evidenced by accumulation of both LC3‐II and p62 expression levels as well as decreased autophagy flux. Its blockade by small interfering RNA attenuated autophagy impairment and reduced palmitate‐induced endoplasmic reticulum stress, apoptosis, and lipid accumulation. Rubicon was also up‐regulated in association with autophagy impairment in livers of mice fed a high‐fat diet (HFD). Hepatocyte‐specific Rubicon knockout mice generated by crossing Rubicon floxed mice with albumin‐Cre transgenic mice did not produce any phenotypes on a normal diet. In contrast, on an HFD, they displayed significant improvement of both liver steatosis and injury as well as attenuation of both endoplasmic reticulum stress and autophagy impairment in the liver. In humans, liver tissues obtained from patients with NAFLD expressed significantly higher levels of Rubicon than those without steatosis. Conclusion: Rubicon is overexpressed and plays a pathogenic role in NAFLD by accelerating hepatocellular lipoapoptosis and lipid accumulation, as well as inhibiting autophagy. Rubicon may be a novel therapeutic target for regulating NAFLD development and progression. (Hepatology 2016;64:1994‐2014).